2006
DOI: 10.1021/jp0662202
|View full text |Cite
|
Sign up to set email alerts
|

Excited-State Proton Transfer in 7-Hydroxy-4-methylcoumarin along a Hydrogen-Bonded Water Wire

Abstract: TDDFT, RI-CC2, and CIS calculations have been performed for the nondissociative excited-state proton transfer (ESPT) in the S1 state of 7-hydroxy-4-methylcoumarin (7H4MC) along a H-bonded water wire of three water molecules bridging the proton donor (OH) and the proton acceptor (C[double bond]O) groups (7H4MC.(H2O)3). The observed structural reorganization in the water-wire cluster is interpreted as a proton-transfer (PT) reaction along the H2O solvent wire. The shift of electron density within the organic chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
59
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 66 publications
4
59
0
Order By: Relevance
“…Therefore, the enol−keto excited-state process corresponds to a HT, not a PT. This is in good agreement with the CIS/SVPD population analysis done by Georgieva et al 43 Table 2. Table 2 indicates that the S 0 tautomerization of C456:3H 2 O in the gas phase is characterized by a high activation energy (0.87 eV), whereas the S 1 state reaction proceeds with a low activation energy (0.23 eV).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, the enol−keto excited-state process corresponds to a HT, not a PT. This is in good agreement with the CIS/SVPD population analysis done by Georgieva et al 43 Table 2. Table 2 indicates that the S 0 tautomerization of C456:3H 2 O in the gas phase is characterized by a high activation energy (0.87 eV), whereas the S 1 state reaction proceeds with a low activation energy (0.23 eV).…”
Section: Resultssupporting
confidence: 92%
“…Georgieva et al extended the investigation by studying the PT reaction in C456 along a H-bonded water wire of three water molecules using TDDFT, RI-CC2, and singly excited configuration interaction (CIS) calculations. 43 The calculations suggest the possibility of HT/PT from the enol to the keto form in the excited state. All of the methods used predict that the reaction path occurs in the π−π* state, and no crossing with a Rydberg-type πσ* state was found.…”
Section: Introductionmentioning
confidence: 90%
“…Moreover, 7-amino 4-methyl coumarin is also used as laser dye and intermediate for the synthesis of bioactive compounds (Nowakowska et al, 2001) and the 4-methylcoumarin derivatives present in various naturally occurring compounds, are known to exhibit a wide range of biological and pharmaceutical activities (Ramesh and Raghunathan, 2008). In addition, coumarin moieties containing hydrazide and sulfonamide groups act as anti-malarial, antiviral activity, anti-HIV, and anticancer agents (Havaldar and Patil, 2008;Hwu et al, 2008;Azizian et al, 2008;Georgieva et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The time-dependent density functional theory (TD-DFT) has been applied to study various 7-aminocoumarins [29][30][31][32][33][34][35][36][37][38][39][40][41][42]. In 2002, Cave et al [29,30] performed a detailed theoretical study on several coumarins using different electronic structure methods and concluded that the TD-DFT method was a powerful tool for treating the spectroscopy of 7-aminocoumarins.…”
Section: Introductionmentioning
confidence: 99%
“…In 2002, Cave et al [29,30] performed a detailed theoretical study on several coumarins using different electronic structure methods and concluded that the TD-DFT method was a powerful tool for treating the spectroscopy of 7-aminocoumarins. More recently, the spectra of a series of coumarins [31][32][33][34][35][36][37][38][39][40][41][42] the TD-DFT method has also been used to study the electronic spectra of the 2,2 0 -bipyridine derivatives [43], the fluorescent material A31 [44] and the TEMPO [45].…”
Section: Introductionmentioning
confidence: 99%